Multi‐cultural values and borders - Nikiforova, Basia (Creativity Studies, 2009)
The presumption of this paper is the view of multi‐culturalism as a concept grounded on an assumption, rather than data, and legitimized by proclamation, rather than legislation. Multi‐culturalism as a socio‐political construction is not only “a multi‐cultural and multi‐religious mosaic”, but it has its own values. The new borders inside the European Union (EU) are non‐territorial, which confirms the new paradigm about the weakening factor of territorial belonging as such. Nowadays, values become a more and more powerful source of demarcation. The aim of this article is to challenge the problem and its consequences for the identity and perception of values in the new European situation, in which borders are merely symbolic. Multi‐culturalism is the revalorization of ethnocentric tradition and the creation of post‐materialist values such as individual self‐expression, personal transformation, openness and solidarity to others, gender and racial equality, greater tolerance for an ethnic, cultural and religious diversity.Daugiakultūrės vertybės ir ribosSantrauka. Daugiakultūriškumas apžvelgiamas kaip konceptas, labiau grindžiamas prielaidomis, o ne žiniomis; įteisinamas diskursu, o ne teise. Daugiakultūriškumas kaip socio-politinis konstruktas nėra vien tik daugiakultūrė ir daugiareligė mozaika – jam būdingos savarankiškos vertybės. Naujos sienos Europos Sąjungoje (ES) yra neteritorinės, jos įtvirtina naują paradigmą, pagrįstą konkretaus teritorinio veiksnio susilpnėjimu. Mūsų dienomis vertybės tampa vis svarbesniu demarkacijos šaltiniu. Šio straipsnio tikslas – iškelti daugiakultūriškumo problemą ir jo įtaką tapatumui bei vertybių suvokimui naujoje Europos situacijoje, kai sienos tėra simbolinės. Daugiakultūriškumas – tai etnocentrinės tradicijos perkainojimas ir kūrimas tokių post-materialistinių vertybių, kaip individuali saviraiška, asmeninė transformacija, atvirumas ir solidarumas, lytinė ir rasinė lygybė, didesnė tolerancija etniniam, kultūriniam ir religiniam skirtingumui.Reikšminiai žodžiai: daugiakultūriškumas, daugiakultūrės strategijos, daugiakultūrės vertybės, religinės ribos, religinis pliuralizmas.First Published Online: 14 Oct 2010